Validation and Testing of STEM Project-Based Virtual Learning Modules to Improve Higher-Level Thinking Skills - Y Yennita; Z Zulirfan; Neni Hermita; Lukman Hakim (JIPF (Jurnal Ilmu Pendidikan Fisika), 2022)
The research objective was to develop a STEM project-based virtual learning module to improve students' higher-level thinking abilities. This research is a Research and Development research by following the steps of the EDDIE model (Analysis, Design, Develop, Implementation and Evaluation). The Analysis stage is an analysis of the initial study on the need for the development of STEM-based Virtual Learning Media. This stage is carried out through survey research. The Design stage is the stage of designing Virtual STEM learning, designing the form of the technology, placing HOT elements, STEM project design, manufacturing techniques, and calculating the size and aesthetics of the media. The Develop stage, making the media into media is declared valid according to the validator, where the validator consists of 2 material experts, 3 media experts, 2 pedagogical experts, and 2 teachers. The Implementation phase is the module testing stage for students. The results obtained were that the project-based STEM virtual learning module was valid with an average assessment score of more than 3. And the results of the module trial on students showed that this module had been declared interesting, useful, and easy to use. The next stage is a project-based virtual STEM module that can be tested through experimental research